Coherent fusion of water array and protonated amine in a metal-sulfate-based coordination polymer for proton conduction - Manna, Biplab; Anothumakkool, Bihag; Desai, Aamod V.; Samanta, Partha; Kurungot, Sreekumar; Ghosh, Sujit K. (Inorganic Chemistry, 2015)
A new function of metal-sulfate-based co-ordination polymer (CP) for proton,conduction Was investigated through rational integration of a continuous water array and protonated amine in the coordination space of the CP. The H-bonded arrays of watet molecules along with nitrogen-rich aromatic cation (protonated melamine) facilitate proton conduction in the compound under humid conditions. Although several reports of metal-oxalate/phosphate-based CPs showing proton conduction are known, this is the first designed synthesis of a metal sulfate-based CP bearing-Water arrays functioning as a solid-state proton conductor:

High hydroxide conductivity in a chemically stable crystalline metal-organic framework containing a water-hydroxide supramolecular chain - Nagarkar, Sanjog S.; Anothumakkool, Bihag; Desai, Aamod V.; Shirolkar, Mandar M.; Kurungot, Sreekumar; Ghosh, Sujit K. (Chemical Communications, 2016)
A chemically stable cationic MOF encapsulating an in situ formed water-hydroxide supramolecular anionic chain is realized for high hydroxide (OH-) ion conductivity in the solid-state (Type A). High OH- ion conductivity and low activation energy of the MOF demonstrate the advantage of the in situ incorporation of OH- ions to achieve efficient OH- ion conduction in the solid-state.

Hydrogen-bonded organic frameworks (HOFs): a new class of porous crystalline proton-conducting materials - Karmakar, Avishek; Illathvalappil, Rajith; Anothumakkool, Bihag; Sen, Arunabha; Samanta, Partha; Desai, Aamod V.; Kurungot, Sreekumar; Ghosh, Sujit K. (Angewandte Chemie-International Edition, 2016)
Two porous hydrogen-bonded organic frameworks (HOFs) based on arene sulfonates and guanidinium ions are reported. As a result of the presence of ionic backbones appended with protonic source, the compounds exhibit ultra-high proton conduction values (sigma) 0.75x 10(-2)Scm(-1) and 1.8x10(-2)Scm(-1) under humidified conditions. Also, they have very low activation energy values and the highest proton conductivity at ambient conditions (low humidity and at moderate temperature) among porous crystalline materials, such as metal-organic frameworks (MOFs) and covalent organic frameworks (COFs). These values are not only comparable to the conventionally used proton exchange membranes, such as Nafion used in fuel cell technologies, but is also the highest value reported in organic-based porous architectures. Notably, this report inaugurates the usage of crystalline hydrogen-bonded porous organic frameworks as solid-state proton conducting materials.
Keywords: guanidinium; hydrogen-bonded organic frameworks; porous crystalline frameworks; proton conduction; sulfonates

Ultrahydrophobic fluorous metal-organic framework derived recyclable composite as apromising platform to tackle marine oil spills - Mukherjee, Soumya; Kansara, Ankit M.; Saha, Debasis; Gonnade, Rajesh; Mullangi, Dinesh; Manna, Biplab; Desai, Aamod V.; Thorat, Shridhar H.; Singh, Puyam S.; Mukherjee, Arnab; Ghosh, Sujit K. (Chemistry-A European Journal, 2016)
Derived from a strategically chosen hexafluorinated dicarboxylate linker aimed at the designed synthesis of a superhydrophobic metal-organic framework (MOF), the fluorine-rich nanospace of a water-stable MOF (UHMOF-100) exhibits excellent water-repellent features. It registered the highest water contact angle (approximate to 176 degrees) in the MOF domain, marking the first example of an ultrahydrophobic MOF. Various experimental and theoretical studies reinforce its distinc-tive water-repellent characteristics, and the conjugation of superoleophilicity and unparalleled hydrophobicity of a MOF material has been coherently exploited to achieve real-time oil/water separation in recyclable membrane form, with significant absorption capacity performance. This is also the first report of an oil/water separating fluorinated ultrahydrophobic MOF-based membrane material, with potential promise for tackling marine oil spillages.

Enhanced proton conduction by post-synthetic covalent modification in a porous covalent framework - Samanta, Partha; Desai, Aamod V.; Anothumakkool, Bihag; Shirolkar, Mandar M.; Karmakar, Avishek; Kurungot, Sreekumar; Ghosh, Sujit K. (Journal of Materials Chemistry A, 2017)
A highly chemically stable porous covalent framework (PCF-1) based on ether linkages has been synthesized, which exhibits no loss up to similar to 500 degrees C along with retention of integrity under acidic, basic and oxidative reagent conditions. Owing to its thermal and chemical stability, post-synthetic covalent modification was executed for the introduction of pendant sulphonic acid (-SO3H) groups. The covalently modified compound (PCF-1-SO3H) presents a remarkably high conductivity (ca. 0.026 S cm(-1)), with an similar to 130 fold enhancement in proton conductivity over the parent compound. This value is comparable with those of commercially used Nafion-based proton conducting materials and stands as the highest known value in the regime of post-synthetically modified porous organic frameworks. It is noteworthy to mention that PCF-1 is stable in both acidic and alkaline media, which is not commonly observed for most of the porous materials trialed as proton conducting materials, including metal organic frameworks.

Ultrahigh ionic conduction in water-stable close-packed metal-carbonate frameworks - Manna, Biplab; Desai, Aamod V.; Illathvalappil, Rajith; Gupta, Kriti; Sen, Arunabha; Kurungot, Sreekumar; Ghosh, Sujit K. (Inorganic Chemistry, 2017)
Utilization of the robust metal-carbonate backbone in a series of water-stable, anionic frameworks has been harnessed for the function of highly efficient solid-state ion conduction. The compact organization of hydrophilic guest ions facilitates water-assisted ion-conduction in all the compounds. The dense packing of the compounds imparts high ion-conducting ability and minimizes the possibility of fuel crossover, making this approach promising for design and development of compounds as potential components of energy devices. This work presents the first report of evaluating ion-conduction in a purely metal-carbonate framework, which exhibits high ion-conductivity on the order of 10(-2) S cm(-1) along with very low activation energy, which is comparable to highly conducting well-known crystalline coordination polymers or commercialized organic polymers like Nafion.